The blackfire blade - Logan, James (Novelist) (Logan, James (Novelist). Last legacy, 2025)
"The hotly anticipated sequel to The Silverblood Promise continues the incredible new epic fantasy series perfect for fans of Scott Lynch. Winter has come early to Korslakov, City of Spires, and Lukan Gardova has arrived with it. Most visitors to this famous city of artifice seek technological marvels, or alchemical ingenuity. Lukan only desires the unknown legacy his father has left for him, in the vaults of the Blackfire Bank. But when Lukan's key to the vault is stolen by a mysterious thief known as the Rook, he and his friends race to win it back-and find themselves trapped in a web of murder and deceit. In desperation, Lukan requests the help of Lady Marni Volkova, scion to Korslakov's most powerful family. Yet Lady Marni has secrets of her own. Worse, she has plans for Lukan and his friends. Plans that involve a journey into Korslakov's dark past, in search of a long-lost alchemical formula that could lead to the city's greatest discovery . . . or its destruction." --